High-Sensitivity Cardiac Troponin I Assay for Early Diagnosis of Acute Myocardial Infarction. (1st July 2019) - Boeddinghaus, Jasper; Nestelberger, Thomas; Twerenbold, Raphael; Koechlin, Luca; Meier, Mario; Troester, Valentina; Wussler, Desiree; Badertscher, Patrick; Wildi, Karin; Puelacher, Christian; du Fay de Lavallaz, Jeanne; Rubini Giménez, Maria; et al.
Abstract: BACKGROUND: The aim of this study was to validate the clinical performance of the Beckman Access high-sensitivity cardiac troponin I (hs-cTnI) assay. METHODS: We enrolled patients presenting to the emergency department with symptoms suggestive of acute myocardial infarction (AMI). Final diagnoses were centrally adjudicated by 2 independent cardiologists with all clinical information including cardiac imaging twice: first, using serial hs-cTnT (Elecsys, primary analysis), and second, using hs-cTnI (Architect, secondary analysis) measurements in addition to the clinically used hs-cTn. hs-cTnI Access was measured at presentation and at 1 h. The primary objective was a direct comparison of diagnostic accuracy as quantified by the area under the ROC curve (AUC) of hs-cTnI Access vs the hs-cTnT Elecsys and hs-cTnI Architect assays. Secondary objectives included the derivation and validation of an hs-cTnI Access-specific 0/1-h algorithm. RESULTS: AMI was the adjudicated final diagnosis in 243 of 1579 (15.4%) patients. The AUC at presentation for hs-cTnI Access was 0.95 (95% CI, 0.94–0.96), higher than hs-cTnI Architect [0.92 (95% CI, 0.91–0.94; P < 0.001)] and comparable to hs-cTnT Elecsys [0.94 (95% CI, 0.93–0.95; P = 0.12)]. Applying the derived hs-cTnI Access 0/1-h algorithm (derivation cohort n = 686) to the validation cohort (n = 680), 60% of patients were ruled out [sensitivity, 98.9% (95% CI, 94.3–99.8)], and 15% of patients were ruled in [specificity, 95.9% (95% CI, 94.0–97.2)]. Patients ruled out by the 0/1-h algorithm had a survival rate of 100% at 30 days. Findings were confirmed in the secondary analyses by the adjudication including serial measurements of Architect hs-cTnI. CONCLUSIONS: Diagnostic accuracy and clinical utility of the Beckman hs-cTnI Access assay are very high and at least comparable to Roche hs-cTnT and Abbott hs-cTnI assays. ClinicalTrials.gov Identifier: NCT00470587.